A novel aptasensor based on single-molecule force spectroscopy for highly sensitive detection of mercury ions. Issue 15 (7th August 2015) - Li, Qing; Michaelis, Monika; Wei, Gang; Colombi Ciacchi, Lucio
<x xml:space="preserve">Abstract</x> A novel aptasensor based on single-molecule force spectroscopy shows high sensitivity and selectivity for sensing mercury ions.